Properties of oil palm frond - plastic composite (elaeis guineensis) / Muhammad Hafiz Abd Kadir - Abd Kadir, Muhammad Hafiz (Faculty of Applied Sciences, 2012)
Plastic composite are being expanded currently. It constructed by composition with wood fiber and plastic. This research is to determine about the mechanical and physical properties of plastic composite from 3 different ratios of wood filler. The small clear specimen of oil palm frond plastic composite was created and separated with S testing that bending, tensile, impact, thickness swelling and water absorption. Small particle give higher result in mechanical properties such as bending, tensile and impact test compared to another size. Besides that, physical properties give inverse result from mechanical properties.